PERAN PENYULUH DALAM BUDIDAYA TANAMAN CABAI DI DESA PONI-PONIKI KECAMATAN TIRAWUTA KABUPATEN KOLAKA TIMUR - Triswanto, Sigit; Musadar, Musadar; Arimbawa, Putu (Universitas Halu Oleo, 2024)
Agricultural extension has a strategic role in the development of chilli farming in Poni-Poniki village, Tirawuta sub-district, East Kolaka district. This research was conducted from February to March 2024 in Poni-Poniki Village with 36 chilli farmers selected by random sampling from 256 chilli farmers. Chilli farmers in Poni-Poniki Village are farmers who are active in conducting Caba farming. Data collection was carried out using survey techniques, observation or observation and documentation. Data analysis used in this study was measured using class intervals. The results showed that based on the discussion of the role of extension workers in the cultivation of chilli plants in poni-poniki village, tirawuta sub-district, east kolaka district showed that farmers' responses to chilli plant cultivation, namely facilitators, motivators and educators, were in the high category.